Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pone.0275572
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in older adults with chronic kidney disease and transient changes in renal function: Findings from the Oxford Renal cohort

Abstract: Background Quality of life (QoL) is an important measure of disease burden and general health perception. The relationship between early chronic kidney disease (CKD) and QoL remains poorly understood. The Oxford Renal Study (OxRen) cohort comprises 1063 adults aged ≥60 years from UK primary care practices screened for early CKD, grouped according to existing or screen-detected CKD diagnoses, or biochemistry results indicative of reduced renal function (referred to as transient estimated glomerular filtration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…However, there were no significant differences in quality of life and symptoms between CCC and renal replacement therapy in their study [ 75 ]. Busa et al [ 76 ]. In a recent investigation by Busa and colleagues (2022), they sought to evaluate the quality of life in older individuals with chronic kidney disease by comparing the utility scores obtained from both ICECAP-A and EQ-5D-5L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were no significant differences in quality of life and symptoms between CCC and renal replacement therapy in their study [ 75 ]. Busa et al [ 76 ]. In a recent investigation by Busa and colleagues (2022), they sought to evaluate the quality of life in older individuals with chronic kidney disease by comparing the utility scores obtained from both ICECAP-A and EQ-5D-5L.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent investigation by Busa and colleagues (2022), they sought to evaluate the quality of life in older individuals with chronic kidney disease by comparing the utility scores obtained from both ICECAP-A and EQ-5D-5L. Their analysis revealed that there were no statistically significant differences in the mean utility scores among different subgroups for EQ-5D-5L or ICECAP-A [ 76 ]. These results align with the findings presented in our study.…”
Section: Discussionmentioning
confidence: 99%